Economic Assesstment of Satellite Remote Sensing Data in Indonesia: A Net Present Value Approach - Diana, Shinta Rahma; Hidayat, Agus; Rafikasari, Astri; Ibrahim, Ida Musdafia; Farida, Farida (International Journal of Economics and Financial Issues, 2019)
This study aims to assess the feasibility of remote sensing activities in Indonesia by using the net present value (NPV) approach. Although these remote sensing activities have been going on for a long time in Indonesia, the economic assessment of the use of remote sensing data has never been done. The research object is remote sensing data of very high, high, medium, and low resolution which has been distributed by The Indonesian National Institute of Aeronautics and Space (LAPAN) to government institution users. The data used for cash inflow is secondary data with a period of 2015 to 2017, while cash outflows are data on investment values from 2013 to 2017. Data analysis uses a qualitative descriptive analysis method based on the calculation of the NPV value generated. The results showed that the remote sensing activity had a positive NPV both in total and by type of resolution. Remote sensing activities in Indonesia deserve to be continued and developed. Keywords: Economic Value, Net Present Value, Remote Sensing, Government Expenditure JEL Classifications: M41, H41, H59 DOI: https://doi.org/10.32479/ijefi.7316